Celts, politics and motivation in archaeology - James, Simon
Ruth & Vincent Megaw questioned the motivation behind the current critique of the use of the term 'Celtic' for the La Téne Iron Age in ANTIQUITY (1996: 175Ð81). They explained it is a nationalist reaction derived from insecurity about modern English identity. Here we have a reply to their paper, whcih rejects these interpretations.